Resiliensi Timotius Bagi Pendidikan dan Penginjilan Masa Kini - Debora Sitohang; Simon Petrus Lumbantoruan; Binsar Simanjuntak; Dapot Damanik (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Education and evangelism in the era of globalization face unprecedented challenges. From technological advances that change the way we communicate to changes in social and cultural values, both are required to remain relevant and effective in fulfilling their purpose. This article explores the concept of ressilience in education and evangelism and strategies for maintaining is relevance and effectiveness in a changing world. Focusing on Timothy’s lifelong adaptability, innovation, and steadfastness, this article aims to provide practical and theoretical insights for today’s educators and evangelists.